Genetic Susceptibility to Periapical Disease: Conditional Contribution of MMP2 and MMP3 Genes to the Development of Periapical Lesions and Healing Response - Menezes-Silva, Renato (2012)
INTRODUCTION: It has been proposed that individual genetic predisposition may contribute to a persistent apical periodontitis condition. Matrix metalloproteinases (MMPs) are associated with levels of inflammation and are involved in caries, pulpal and periapical tissue destruction. MMPs also play a major role in bone resorption. In this study, we hypothesized that polymorphisms in MMP genes and their regulators may contribute to an individual's increased susceptibility to apical tissue destruction in response to deep carious lesions. METHODS: Sixteen hundred radiographic records obtained through the University of Pittsburgh School of Dental Medicine Dental Registry and DNA Repository were screened for subjects with deep carious lesions in dentin with or without periapical lesions (≥3mm). DNA samples of 268 patients were sorted into two groups: 158 cases with deep carious lesions but no periapical lesions (controls), and 110 cases with periapical lesions and deep carious lesions (cases). Sixteen SNP markers in MMP2, MMP3, MMP9, MMP13, MMP14, and TIMP2, were selected for genotyping. Genotypes were generated by end-point analysis in a Real Time PCR instrument. Analyses were performed comparing cases and controls. Allele and genotypic frequencies and haplotype analysis were calculated using PLINK program. RESULTS: Association was found for MMP3 rs639752 (p=0.03) and rs679620 (p=0.004) genotypes in individuals with periapical lesions. We also observed altered transmission of MMP2 marker haplotypes (p=0.000004) in these individuals. CONCLUSION: Variations in MMP2 and MMP3 are associated with periapical lesion formation in individuals with untreated deep carious lesions. Future studies could help predict host susceptibility to developing periapical lesions.